Apakah Nikel Indonesia Memiliki Keunggulan Daya Saing di Pasar Internasional? - Edy Suryanto (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2022)
International trade is one of the fundamental ways to overcome the unequal distribution of goods or services to meet each country's needs. Nickel is a non-renewable natural resource, but its existence is always needed in various countries. Indonesia's decision to ban nickel ore in 2014 impacted the scarcity of nickel in importing countries. This study aims to analyze the competitiveness of Indonesian nickel ore commodities in the international market. Three variants of the approach in the form of X/M Ratio analysis techniques, Revealed Comparative Advantage (RCA), and Trade Specialization Index (TSP) are used to determine the value of competitiveness in the global market. This study uses secondary data in the form of time series data with a span of the last five years to describe the comparative advantage of Indonesian nickel ore from time to time. Meanwhile, in 2016 and 2020, it did not have an advantage due to the export ban policy by the Indonesian government. The Trade Specialization Index (TSP) approach found that in 2017, 2018, and 2019 Indonesia was at the stage of maturation of nickel ore exporters. This study suggests that the Indonesian government should optimize the production of nickel ore products that have been added to compete in the global market. Furthermore, the government must also be able to attract foreign investment to establish an iron ore smelter in Indonesia.